2019
DOI: 10.1074/jbc.ra119.008649
|View full text |Cite
|
Sign up to set email alerts
|

AMPK and AKT protein kinases hierarchically phosphorylate the N-terminus of the FOXO1 transcription factor, modulating interactions with 14-3-3 proteins

Abstract: Edited by Wolfgang Peti Forkhead box protein O1 (FOXO1) is a transcription factor involved in various cellular processes such as glucose metabolism, development, stress resistance, and tumor suppression. FOXO1's transcriptional activity is controlled by different environmental cues through a myriad of posttranslational modifications. In response to growth factors, the serine/threonine kinase AKT phosphorylates Thr 24 and Ser 256 in FOXO1 to stimulate binding of 14-3-3 proteins, causing FOXO1 inactivation. In c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(59 citation statements)
references
References 52 publications
3
54
0
Order By: Relevance
“…Furthermore, FoxO1 acetylation permits access for upstream kinases to phosphorylate its Ser 253 residue that is otherwise shielded by FoxO1-DNA complex formation (Matsuzaki et al 2005). FoxO1 phosphorylation sites have since became known to act as docking or shielding sites for 14-3-3 protein binding, and the heterodimer exit into and retention within the cytoplasm (Brunet et al 1999;Saline et al 2019).…”
Section: Regulation Of Transcription Factors Involved In Autophagy Gementioning
confidence: 99%
“…Furthermore, FoxO1 acetylation permits access for upstream kinases to phosphorylate its Ser 253 residue that is otherwise shielded by FoxO1-DNA complex formation (Matsuzaki et al 2005). FoxO1 phosphorylation sites have since became known to act as docking or shielding sites for 14-3-3 protein binding, and the heterodimer exit into and retention within the cytoplasm (Brunet et al 1999;Saline et al 2019).…”
Section: Regulation Of Transcription Factors Involved In Autophagy Gementioning
confidence: 99%
“…2 b), and Cys457 and Cys612 show particularly high conservation. A structural analysis indicated that Cys457 of FOXO1 is located in an important functional region [20] , which suggests that Cys457 is closely related to FOXO1 activity and might be persulfidated by H 2 S. As a result, we transfected WT and C457S-mutated FOXO1 plasmids into VSMCs and 293T cells and found that NaHS significantly persulfidated FOXO1 in the cells transfected with WT FOXO1 but could not persulfidate FOXO1 in the cells transfected with C457S FOXO1 ( Fig. 2 c and 2d).…”
Section: Resultsmentioning
confidence: 99%
“…To determine the exact site persulfidated by H 2 S, we first performed a sequence homology analysis of FOXO1 proteins from seven species and revealed that the cysteine residues were conserved in FOXO1 proteins from different species and that Cys457 and Cys612 were highly conserved among the seven species. Cys457 in FOXO1 is reportedly located in the transcriptional activation domain (aa 421–655) of FOXO1 [20] and in the functional region (aa 283–563) of FOXO1, which interacts with Nemo-like kinase (NLK), as described in the UniProt database. Previous studies have reported that NLK activates FOXO1 phosphorylation, FOXO1 nuclear exclusion to the cytoplasm and inhibits FOXO1 transcriptional activity [32] , which suggests that Cys457 is crucial for FOXO1 activity.…”
Section: Discussionmentioning
confidence: 99%
“…The carbohydrate-responsive element-binding protein (chreBP) has a crucial role in the regulation of hepatic lipogenesis, hepatic steatosis and insulin resistance (21,22). chreBP is a major mediator in glycolysis and lipogenesis via binding to the promoter region of lipogenic genes.…”
Section: Trimetazidine Improves Hepatic Lipogenesis and Steatosis Inmentioning
confidence: 99%